The Effect of Qiweibaizhu Powder Crude Polysaccharide on Antibiotic-Associated Diarrhea Mice Is Associated With Restoring Intestinal Mucosal Bacteria - Li, Cuiru; Zhou, Kang; Xiao, Nenqun; Peng, Maijiao; Tan, Zhoujin (Frontiers in Nutrition, 2022)
Background: Qiweibaizhu powder (QWBZP) has been shown to be effective in treating antibiotic-associated diarrhea (AAD). Previous research has reported that plant polysaccharides can promote the growth of beneficial intestinal bacteria and inhibit the multiplication of pathogenic bacteria, thus effectively treating diarrhea. Here, we investigated the effect of QWBZP crude polysaccharide on the diversity of intestinal mucosal bacteria and its community structure composition in mice with AAD and to provide the scientific basis for the efficacy of QWBZP crude polysaccharide on diarrhea. Material and Methods: Eighteen KM mice were randomly divided into the normal group (mn), model group (mm), and QWBZP crude polysaccharide treatment group (ma), with six mice in each group. An AAD model was constructed using a mixed antibiotic solution and treated with gavage crude polysaccharide solution of QWBZP. The intestinal mucosa was extracted from the jejunum to the ileum of mice, and the metagenome was extracted, then analyzed by Miseq sequencing to characterize the intestinal mucosal bacteria of mice. Results: The spleen and thymus indices in each group of mice were no significant differences. The Chao1 and ACE indices of the mn and mm groups were similar, the Simpson index was the largest and the Shannon index was the smallest in the mm group, and there was no significant difference in the diversity indices of all three groups. In the PCA and Pcoa, the mn and ma group samples were both relatively concentrated with high similarity of community structure. In contrast, the samples of the mm group were more scattered and farther away from the samples of the mn and ma group, i.e., the community structure similarity within and between the groups was low. Compared with the mm group, the relative abundance of Proteobacteria, Lactobacillus, and the Firmicutes/Bacteroidetes (F/B) ratio in the ma group were decreased, while the Enterococcus continued to increase. In the LEfSe analysis, there were significant differences in the characteristic bacteria of the mn, mm, and ma groups. Conclusion: The single crude polysaccharide component is not very effective in treating AAD, so the clinical efficacy of the QWBZP crude polysaccharide is subject to further investigation.